Connection between the potential wind energy and the windy days - Tar, Károly; Tóth, Tamás; Rózsavölgyi, Kornél (Acta Geographica Debrecina Landscape & Environment series, 2008)
Preliminary wind climate information are required for the selection of the sites of energetic wind measurements. Optimal locations of wind energy projects, where the amount of utilizable wind energy can be forecasted with a good approach, can be determined using GIS and statistical methods. Anyhow, it is necessary to elaborate methods what make posible to gain data for the wind potential of a given location on the base of measured data. Monthly number of windy days can be such predictor if its basic statistical parameters and its connection to the monthly mean wind power can be determined. This latter one can be substituted by the area under the curve of the function fitted to the hourly averages of the cubes of the wind speeds. A regression modell is fitted to the monthly number of windy days and areas under the curve, on the base of time series of 7 Hungarian weather stations and the error of the modell is determined. On this base, the modell is extrapolated to a 35 years long period. The area under the curve proportional to the monthly mean wind power calculated on the base of the monthly number of windy days show a significant decreasing trend in 4 Hungarian weather stations.